Implementasi Green Economy dalam mewujudkan Pembangunan Berkelanjutan dalam perspektif Maqashid Syariah - Abimayu, Alben; Anas Malik; Rosydalina Putri (Institut Agama Islam Negeri Kendari, 2025)
This study aims to analyze the implementation of green economy principles in supporting sustainable development from the perspective of maqāṣid al-sharī‘ah at PT Lestari Banten Energi (LBE), Indonesia. Using a qualitative descriptive design, this study was conducted at the LBE site in Serang Regency, Banten Province, between March and June 2024. Data were obtained through in-depth interviews, observations, and documentation, supplemented by secondary sources such as company reports and policy documents. The analytical lens operationalized the five dimensions of maqāṣid al-sharī‘ah religion (hifzh al-dīn), life (hifzh al-nafs), intellect (hifzh al-‘aql), progeny (hifzh al-nasl), and wealth (hifzh al-māl) into indicators in the environmental, social, and economic domains. The results show that in the environmental field, LBE manages hazardous waste (fly ash and bottom ash) into building materials and maintains green open spaces to preserve the ecosystem. In the social field, the company's CSR programs in education, health, religion, animal husbandry, sports, and culture have improved the quality of life of the local community. In the economic sphere, a fair wage system and community empowerment through livestock programs have promoted inclusive prosperity. These practices are concretely aligned with the values of maqāṣid al-sharī‘ah, demonstrating the synergy between sustainability and Islamic ethics. This study concludes that the integration of maqāṣid-based green economy principles strengthens corporate sustainability governance and can serve as a policy model for similar industries in Indonesia.